Effect of waterlogging on morphological changes and growth of six forage grasses - Phengpet, Suphaphan; Hare, Michael; Terapongtanakorn, Suwat; Wongpichet, Kitti (วารสารแก่นเกษตร, 2016)
Waterlogging from successive rain depressions causes problems for forage grasses in the low lying areas of northeast Thailand. Six promising forage grass cultivars [Ubon paspalum (Paspalum atratum cv. Ubon), Mombasa guinea (Panicum maximum cv. Mombasa), Purple guinea (P. maximum cv. Purple), Mulato II (Brachiariaruziziensis x B. decumbens x B. brizantha cv. Mulato II), Cayman (B. ruziziensis x B. decumbens x B. brizantha cv. Cayman), and humidicola (B. humidicola)] were studied for waterlogging tolerance. The objectives were to evaluate these forage grasses on 1) the effect of waterlogging at late vegetative phase on morphological changes and growth; and 2) the effect of repeated waterlogging (with 30 days recovery period) at the late vegetative phase on morphological changes and growth. The results showed that: 1) Waterlogged grasses had yellow and dried out leaves and more adventitious roots; plant height, number of tillers, and leaf area were lower (P < 0.05); and total dry weight started to lower at 40 days of waterlogging compared to those of control (P < 0.05). Ubon paspalum tolerated best to waterlogging followed by humidicola, Cayman, Purple guinea, Mombasa guinea; while Mulato II was the most susceptible. 2) Repeated waterlogging with recovery period caused yellowish and dried out leaves, stimulated the production of adventitious roots, new leaves, and new shoots. Plant height was higher, but the number of tillers and leaf area were lower compared to those of control (P < 0.05). Waterlogging once with recovery period seemed to do no harm on grasses; but repeated waterlogging with recovery period as well reduced total dry weight (P < 0.05). Humidicola tolerated best to repeated waterlogging followed by Ubon paspalum, Cayman, Purple guinea, Mombasa guinea; while Mulato II was most susceptible.